EVALUATION OF THE ANTIFUNGAL ACTIVITY OF HEXANIC AND METHANOLIC EXTRACTS OF PURPLE IPÊ (HANDROANTHUS IMPETIGINOSUS) AGAINST CANDIDA ALBICANS AND ASPERGILLUS BRASILIENSIS (CIPEEX, 2025)
Purple Ipê (Handroantus impetiginosus) is widely known for its phytotherapeutic properties and for the treatment of various pathologies, despite the lack of clarity about its medicinal mechanisms. This study investigated the antifungal activity of purple Ipê extracts using the Minimum Inhibitory Concentration (MIC) technique in vitro. The present study aimed to gather information on the feasible and cost-effective potential of new antifungal activities derived from purple Ipê extracts against Aspergillus brasiliensis and Candida albicans. However, no significant results were obtained, so there was no motivation to proceed with in vivo research on larvae. It is concluded that further studies should be conducted to explore alternative effective extraction methods of purple Ipê in combination with bioactive compounds to harness its therapeutic potential in clinical contexts.
Keywords: purple ipê; Tenebrio molitor; antifungal activity